Efektivitas Limbah Cair Pemindangan Ikan dalam Ransum terhadap Performan Itik Persilangan Mojosari Peking - Achmad Sifai; Luthfi Djauhari Mahfudz; Warsono Sarengat (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The aim of this research was to examined the effectiveness of the used of liquid waste fish preservation in the ration on performance of Mojosari – Pekin crossing duck age 3 - 8 weeks. The material used 120 of male Mojosari - Pekin crossing ducks 3 weeks with an average body weight of 520.30 ± 57.82 g. The experimental design used was Completely Randomized Design (RAL) with 4 treatments and 5 replications, each replications consisted of 6 ducks. The treatment used of liquid waste fish preservation as follows: T0 = 0%, T1 = 2.5%, T2 = 5% and T3 = 7.5%. The data obtained were analyzed using analysis of variance and F test at 5% level then continued Duncan double area test if there was effect of treatment. The results showed that the use of liquid waste fish preservation up to 7,5% level did not have significant effect (P>0,05) on ration consumption, body weight gain and ration conversion, but income over feed cost (IOFC) increased with the use of liquid waste fish preservation up to 5% level. The conclusion of this research is the most effective using liquid waste fish preservation is 2,5%.